Seroepidemiology of amoebiasis in the villagers in Phichit province and urban slum dwellers in Bangkok, Thailand - T. Bunnag (2018)
A serological survey was conducted in the villages of Phichit Province, Northern region and in the urban slum communities in Bangkok to determine whether amoebiasis was endemic in the areas and to determine the prevalence rates. Six rural villages, ethnically and culturally alike with a population of 3,019 and two urban slums with a population of 1,510 were surveyed. Sera were tested for indirect hemagglutination antibody (IHA) to Entamoeba histolytica and the stools examined for the parasite by direct smear method. Positive IHA titres (≥1 : 128) were detected in 482 (11%) and 176 (20%) sera, and E. histolytica found in 639 (2%) and 208 (3%) stool specimens of rural and urban slum populations respectively. Out of a total of 88 persons who showed significant levels of IHA antibodies to E. histolytica antigen, 5 had E. histolytica cysts in their stool specimens. The survey confirmed, serologically and parasitologically, that ameobiasis is endemic in the lower socio-economic areas. Substandard living and sanitary conditions within the areas were considered responsible for the transmission of the disease.